EUROPEAN PERSPECTIVES OF INTERNATIONAL ECONOMIC INTEGRATION OF UKRAINE - Viktoriia Zalizniuk; Galina Artamonova (Baltic Journal of Economic Studies)
The article explores the key opportunities and risks faced by Ukraine on its path toward European integration under the current conditions of Russia's full-scale aggression against Ukraine. The status of a candidate for EU membership engenders a plethora of opportunities and advantages for the country, particularly by enhancing the prospects established in the Association Agreement and other sectoral agreements between Ukraine and the EU. The present study analyses the structure and dynamics of Ukraine's foreign trade with European countries, focusing on the demand within the EU for Ukrainian agri-food products, which currently represent the leading category of Ukraine's exports to Europe. The study examines the complex conditions under which Ukraine's agricultural potential is developing and identifies the main external and internal risks affecting the further expansion of foreign trade in agricultural and food products with EU Member States. Moreover, it underscores the challenges associated with trade liberalisation within the EU framework, in addition to the pace and nature of Ukraine's economic integration with European markets. The role of institutional development and public administration in the context of Ukraine's European integration is a subject to which particular attention is devoted. The analysis explores how reforms in the rule of law, anti-corruption initiatives, and the modernisation of public institutions impact Ukraine's prospects for integration into the European market. The article also addresses the key challenges confronting the country's administrative structures, such as ensuring economic resilience, maintaining a stable regulatory environment, and enhancing the efficiency of state governance. The mechanisms by which to attract foreign investment and to improve Ukraine's credibility among European partners are examined, with particular emphasis on the significance of institutional co-operation between Ukraine and the EU. This encompasses aspects such as legal harmonisation, the implementation of European governance practices, and the effective operation of the labour market. Moreover, the article considers the specific challenges of implementing the European integration agenda during wartime in Ukraine. The primary risks identified in this context encompass the duration and conduct of the full-scale war, disruptions in trade and logistics with the EU, active opposition by the Russian Federation to Ukraine's European aspirations, and the absence of full consensus among EU member states regarding Ukraine's accession. Other risks include the gradual decline in EU interest in supporting Ukraine's integration, the slowdown of critical reforms (particularly in the areas of the judiciary, law enforcement, anti-corruption, and public administration), the shortage of qualified specialists in European integration, and the limited involvement of local governments. The article concludes that the restoration of peace and stability is imperative for the continued development of economic relations between Ukraine and the EU.